ANTIBIOTIC SENSITIVITY OF BACTERIAL BLOODSTREAM INFECTIONS IN THE INTENSIVE CARE UNIT PATIENTS OF UNIVERSITY HOSPITALS IN SANA’A CITY, YEMEN - Al-Yosaffi, Eshtiaq A; Al-Shamahy, Hassan Abdulwahab; Othman, Arwa Mohammed; Al-Haddad, Ahmed Mohammed; Al-Moyed, Khaled Abdulkarim (Universal Journal of Pharmaceutical Research, 2023)
Aim: High rates of morbidity and mortality are associated to bacterial bloodstream infections (B-BSI) in many hospitals, especially in the intensive care unit. This study investigated the prevalence of antibiotic- and multidrug-resistant bacteria isolated from blood samples of patients in intensive care units of university hospitals in the city of Sana’a, Yemen. Subjects and methods: A cross-sectional study was conducted on sepsis patients admitted to intensive care units in four hospitals in Sana’a, Yemen, between January 1 and April 30, 2022. The blood cultures of patients suspected of suffering from sepsis were performed. The potential bacterial pathogens were isolated and identified using standard laboratory methods, and microbial susceptibility testing was performed using the disk diffusion technique. Results: For all identified bacteria, the average resistance rate to a broad spectrum of antibiotics tested ranged from 22.5% to 98.1%, with cefazoline (98.1%) having the greatest resistance rates, followed by amoxicillin (87.2%) and cefixime (83%). Vancomycin had a resistance rate of 4.8% whereas erythromycin had a resistance rate of 75% for Gram-positive bacteria. For Gram-negative bacteria, the resistance rates to narrow spectrum antibiotics ranged from 2.3% for colistin sulphate to 84.8% for aztreonam. Our isolates’ MDR rates for resistance to at least three classes of antibiotics were 52.2% and 8.7%, respectively, for resistance to 10 different classes of broad-spectrum antibiotics and their subclasses. Conclusion: Gram positive bacteria are highly resistant to erythromycin and penicillin, while gram negative organisms are highly resistant to amoxcillin+clavulanic acid, ciprofloxacin, and all generations of cephalosporins. This study highlights the significance of prompt clinical and bacteriological monitoring among patients in critical care conditions, such as ICU patients, and also illustrates the establishment and rates of Multi Drug Resistance (MDR) pathogens. Peer Review History: Received: 4 August 2023; Revised: 8 September; Accepted: 27 October; Available online: 15 November 2023 Academic Editor: Dr. Asia Selman Abdullah , Pharmacy institute, University of Basrah, Iraq, asia_abdullah65@yahoo.com Reviewers: Dr. Tamer Elhabibi, Suez Canal University, Egypt, tamer_hassan@pharm.suez.edu.eg Dr. Wadhah Hassan Ali Edrees, Hajja University, Yemen, edress2020@gmail.com